2008
DOI: 10.1097/wnr.0b013e32831269be
|View full text |Cite
|
Sign up to set email alerts
|

Attention-related modulation of auditory brainstem responses during contralateral noise exposure

Abstract: As determinants facilitating attention-related modulation of the auditory brainstem response (ABR), two experimental factors were examined: (i) auditory discrimination; and (ii) contralateral masking intensity. Tone pips at 80 dB sound pressure level were presented to the left ear via either single-tone exposures or oddball exposures, whereas white noise was delivered continuously to the right ear at variable intensities (none--80 dB sound pressure level). Participants each conducted two tasks during stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Inconsistent with the findings of Woldorff et al, Ikeda et al ( 2008 ) showed that selective attention affected tone-pip ABRs (Figure 4 ). A task requirement of perceptual discrimination between pips of a target frequency and a non-target frequency, alongside rather loud (100 dB SPL) contralateral masking noise, sufficed to cause attentional augments of ABRs.…”
Section: The Rostral Brainstem As a Computational Hub In The Ascendinsupporting
confidence: 81%
“…Inconsistent with the findings of Woldorff et al, Ikeda et al ( 2008 ) showed that selective attention affected tone-pip ABRs (Figure 4 ). A task requirement of perceptual discrimination between pips of a target frequency and a non-target frequency, alongside rather loud (100 dB SPL) contralateral masking noise, sufficed to cause attentional augments of ABRs.…”
Section: The Rostral Brainstem As a Computational Hub In The Ascendinsupporting
confidence: 81%
“…Naturally, we cannot exclude a possible earlier-latency effect, since attentional modulation can be seen at brainstem [36], [37], and even lower level (see [12]). We could not, however, reliably quantify the 50-ms response due to poor signal-to-noise with the narrowest notches (see Fig.…”
Section: Discussionmentioning
confidence: 96%
“…That is, Ikeda et al [1] have revealed selective attentional influences upon ABRs: In contralateral loud (100 dB SPL) noise, rare "deviant" target tone pips to the left ear exhibited a positivity in the range of waves II-VI. In addition, there were selective attentional decrements in ABRs to attended frequent "standard" non-target tone-pips relative to acoustically identical sounds that participants just ignore [1]. In quieter contralateral noise (80 dB SPL)…”
Section: Attention and Abrsmentioning
confidence: 99%
“…On corticopetal-corticofugal loops of the new early filter: From cell assemblies to the rostral brainstem Selective attention affects both thalamocortically generated auditory middlelatency responses and cortically generated auditory long-latency responses, yet, up until the work of Ikeda et al [1][2][3], no such attentional effects upon auditory brainstem responses (ABRs) had been observed [4][5]. That is, Ikeda et al [1] have revealed selective attentional influences upon ABRs: In contralateral loud (100 dB SPL) noise, rare "deviant" target tone pips to the left ear exhibited a positivity in the range of waves II-VI. In addition, there were selective attentional decrements in ABRs to attended frequent "standard" non-target tone-pips relative to acoustically identical sounds that participants just ignore [1].…”
Section: Attention and Abrsmentioning
confidence: 99%
See 1 more Smart Citation